Alternatives to Synthetic Herbicides for Weed Management in Container Nurseries - Gary W. Knox; Matthew Chappell; Robert H. Stamps (EDIS)
Weed management is one of the most critical and costly aspects of container nursery production. This is most effectively achieved through preventative practices, primarily with preemergent herbicides. But there are valid reasons for managing weeds with alternatives to synthetic herbicides, including sanitation, exclusion, prevention, hand weeding, mulching, and the use of cover crops, heat, and nonsynthetic herbicides. This 6-page fact sheet was written by Gary W. Knox, Matthew Chappell, and Robert H. Stamps, and published by the UF Department of Environmental Horticulture, September 2012.